2015
DOI: 10.3892/etm.2015.2574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bone marrow stem cell mobilisation on the expression levels of cellular growth factors in a rat model of acute tubular necrosis

Abstract: Abstract. The aim of the present study was to observe the mobilisation effects of stem cell factor (SCF) and granulocyte colony-stimulating factor (G-CSF) on bone marrow stem cells (BMSCs) in rats with renal ischaemia-reperfusion injury. In addition, the effects of the BMSCs on the expression levels of hepatocyte growth factor (HGF) and epidermal growth factor (EGF) were investigated, with the aim to further the understanding of the protective mechanisms of SCF and G-CSF in renal ischaemia-reperfusion injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This can lead to an increased cellular growth factor expression, thus triggering cell regeneration in the renal tubules after the ischemiareperfusion injury. 15,16 Furthermore, Zhuo et al in 2017 showed that stem cell administration into the renal could restore the balance between the existing antioxidant and oxidant inside the ischemic renal. 17 In this study, stem cell therapy was able to prevent and restore cell damage that was caused by ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to an increased cellular growth factor expression, thus triggering cell regeneration in the renal tubules after the ischemiareperfusion injury. 15,16 Furthermore, Zhuo et al in 2017 showed that stem cell administration into the renal could restore the balance between the existing antioxidant and oxidant inside the ischemic renal. 17 In this study, stem cell therapy was able to prevent and restore cell damage that was caused by ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%